Análise dos impactos causados por problemas logísticos na Fórmula 1 - Moreira, Felipe Danna (My University, 2022)
Throughout the event of globalization, access to the most diverse types of entertainment has been facilitated. In this context, motor sports have gained the appreciation and admiration of a considerable part of the world population. Formula 1 represents the pinnacle of motorsport and nowadays encompasses, in a single season, 23 Grand Prix. Each of these events is meticulously planned, considering the essential preparation necessary to sustain a season that, as in 2022, will pass through 21 countries and four continents, over eight months. With this in mind, combined with the growth and popularization of the sport, it is possible to notice the prominent position and evidence of the category at a global level. This visibility is particularly noticeable after the growth that Formula 1 has achieved since it was acquired and started to be controlled by Liberty Media, a company that invested in the modernization of the sport and helped to spread it around the globe. In addition, largely due to the internationalization and popularization of the sport, there is a permanent propagation of information, facilitating the necessary access for research purposes. Given this context, the present paper aimed to analyze the impacts caused by logistical problems in Formula 1, in order to facilitate an understanding of the performance of logistical processes at their highest levels of demand. Therefore, a research was carried out with a predominantly qualitative approach, of a descriptive nature. Secondary data has been collected from documents and reports available on the official websites of Formula 1 and its partners, as well as works and articles that report the problems present in the logistical scope of the automobile category to help carry out the paper. The results indicated that the Formula 1 logistics is very specific and dynamic, requiring adequate planning made in advance. Direct and indirect problems are present in this scope, which requires greater proactivity on the part of organizations, which must be prepared to suffer the least possible impacts. In parallel, points that also collaborate with the mitigation of possible logistic complications are communication, synergy and the support present between all parties involved. [resumo fornecido pelo autor]
Através do evento da globalização, vem ocorrendo uma facilitação de acesso aos mais diversos tipos de entretenimento. Nesse âmbito, os esportes a motor ganharam o apreço e a admiração de uma fatia considerável da população mundial. A Fórmula 1 representa o ápice do automobilismo e chega a abranger, em uma única temporada, 23 Grandes Prêmios. Cada um desses eventos é meticulosamente planejado, considerando o imprescindível preparo necessário para sustentar uma temporada que, como em 2022, passará por 21 países e quatro continentes, ao longo de oito meses. Tendo isso em vista, aliado ao crescimento e popularização do esporte, é possível observar a posição de destaque e evidência da categoria em nível global. Essa visibilidade é notada principalmente após o crescimento que a Fórmula 1 alcançou desde que foi adquirida e passou a ser controlada pela Liberty Media, empresa que investiu na modernização do esporte e auxiliou a difundi-lo. Ademais, muito por conta da internacionalização e popularização do esporte, ocorre uma permanente propagação de informações, facilitando o acesso necessário para fins de pesquisa. Dado esse contexto, o presente trabalho teve como objetivo analisar os impactos causados por problemas logísticos na Fórmula 1, de modo a possibilitar a compreensão acerca do desempenho dos processos logísticos em seus mais altos níveis de exigência e performance. Para tanto, foi realizada uma pesquisa com abordagem predominantemente qualitativa, de natureza descritiva. Para a realização do trabalho foram coletados dados secundários, de documentos e relatórios disponíveis nos sites oficiais da Fórmula 1 e seus parceiros, bem como obras e artigos que relatam os problemas presentes no âmbito logístico da categoria automobilística. Os resultados indicaram a logística da Fórmula 1 é muito específica e dinâmica, exigindo planejamento adequado e com alta antecedência. Problemas diretos e indiretos estão presentes nesse âmbito, o que requer maior proatividade por parte das organizações, devendo as mesmas estarem preparadas para sofrer os menores impactos possíveis. Em paralelo, pontos que também colaboram com a mitigação de eventuais complicações logísticas são a comunicação, sinergia e o respaldo presente entre todas as partes envolvidas. [resumo fornecido pelo autor]
Keywords: Logística; Comércio internacional; Corridas de automóveis